Pendekatan Komunikatif (Communicative Approach) dalam Pembelajaran Bahasa Inggris - Uzer, Yuspar; Uzer, Yus Vernandes (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The Communicative Approach is an approach that focuses on active and practical communication skills. According to language observers, this approach has made a new strategic breakthrough in the field of second language teaching, and is considered an integral approach and has definite characteristics. This is because of the combination of strategies that are based on a certain definite goal, namely training to use language spontaneously and creatively. Language has a central role in the intellectual, social and emotional development of students and is a supporter of success in studying all fields of study. Learning English has a very important role not only in developing communication skills but also for the sake of mastering knowledge. Through language, humans learn various kinds of knowledge that exist in the world. In the school context, students use language not only for language learning purposes but also to learn various kinds of knowledge taught at school.